INTERNALISASI PENDIDIKAN SEKS TERHADAP ANAK PEKERJA MIGRAN DI KABUPATEN BLITAR - Luvi Mei Anggraini; Irawan Irawan; Joan Hesti Gita Purwasih (Jurnal Antropologi: Isu-Isu Sosial Budaya, 2021)
Social changes that make society can influence the apparatus. Social changes have an impact on families in Indonesia. The narrower the workforce is coupled with the increasing needs of the family, the older the migrant worker works. As a result, the roles and functions of the family do not work properly. The impact is that the children commit juvenile delinquency. Like it or not, parents still guide their children and understand sexual education so that children do not engage in deviant behavior. This research method uses descriptive qualitative methods. The research focuses on how migrant workers instill sex education in children. There were six informants including 3 migrant workers and 3 migrant workers. Data techniques are observation and open interviews. The results of this study indicate that each migrant worker has a way of imparting sexual education to children. Differences in the cultivation of character education are motivated by several factors. One of them is the cultural factor of the country where the parents work. Furthermore, the acceptance of children in sex education and its application is almost similar. Children still maintain the limits of norms that apply in society.